OECD compatible trade and production data base - Brodin, Anders (OECD ParisFR, 1986)
Contains animal statistics on production, imports and exports of manufactured goods of OECD countries. Production and trade statistics are classified according to the International Standard Industrial Classification nomenclature. Describes some of the analytic uses to which the contents of the database can be put and discusses some of the problems encountered in setting up this database